HUBUNGAN GERAKAN BERULANG DAN POSTUR KERJA POSISI TANGAN TERHADAP KEJADIAN DE QUERVAIN’S TENOSYNOVITIS SYNDROME PADA BURUH SORTASI BIJI KOPI ( Studi Kasus Pada Buruh Sortasi Biji Kopi di PT. X ) - Faricha Nur Amanda; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2020)
De Quervain's Tenosynovitis Syndrome (DQT) is a type of Occupational Disease in the group of Musculoskeletal Disorders which is characterized by inflammation of the wrist side in the thumb, precisely on the tendon of the musculus extensor pollis brevis and musculus abductor pollicis longus due to trauma or loading that is too heavy, with typical symptoms such as pain, numbness, and tingling in the thumb to the wrist. Repetitive movements, hand posture, direct trauma, and joint inflammation are risk factors that can cause DQT. In the plantation sector, especially coffee sorter workers who are tasked with manually sorting coffee beans using workers' hands continuously and for long periods of time can cause workers to experience pain complaints on the body parts of workers, especially the fingers to wrists workers can thus be at risk of experiencing DQT. The purpose of this research is to analyze the association between repetitive movements and working postures of hand positions on the occurrence of DQT in workers sorted coffee beans in PT X. The  type of this research is quantitative research with cross sectional study approach. This research uses the BRIEF Survey to measure hand work posture, the Finkelstein Test to determine the incidence of De Quervain's Syndrome, and the VAS Sheet (Visual Analoque Scale) to describe pain complaints subjectively based on the results of the Finkelstein test. The population and research sample in this study were 53 workers. Based on statistical tests using Chi-Square, there was an association between repetitive movements in the right and left hand with DQT (p value = 0.001) and there was no association between work posture of the hand position with DQT (p value = 0.231). Some recommendation for field supervisors sompany are to be able to provide education and practice on the application of muscle stretching procedures especially on the fingers and wrists. Workers should routinely stretch the fingers and wrists both before and during work, and after work.